A theoretical and experimental study of the boundary layer flow on a 45 degrees swept back wing - Burrows, F. M. (College of Aeronautics, Cranfield, 1956)
In this paper an account is presented of a theoretical and experimental study made in relation to the boundary layer flow on a 45 degree swept back wind. Continues...